Cyclodextrin-Modified CeO(2) Nanoparticles as a Multifunctional Nanozyme for Combinational Therapy of Psoriasis - Wu, Lingyun (Int J Nanomedicine, 2020)
PURPOSE: Reactive oxygen species (ROS)-induced oxidative stress plays a key role in the pathogenesis and progression of psoriasis by causing inflammation. Antioxidative strategies eradicating ROS may serve as effective and easy treatment options for psoriasis, while nanozymes with intrinsic antioxidant enzyme-like activity have not been explored for psoriasis treatment. The aim of this study is to fabricate β-cyclodextrins (β-CDs)-modified ceria nanoparticles (β-CDs/CeO(2) NPs) with drug-loaded and multimimic-enzyme activities for combinational psoriasis therapy. METHODS: The β-CDs/CeO(2) NPs were synthesized by a hydrothermal method using unmodified β-CDs as a protecting agent. The structure, size and morphology were analyzed by dynamic light scattering, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) spectroscopy. Considering the superoxide dismutase (SOD)- and catalase-mimetic activities, the in vitro antioxidant activity of the β-CDs/CeO2 NPs was investigated. After dithranol (DIT) was loaded, the drug-loading capacity and release profile were determined by UV-visible light spectrophotometer and high-performance liquid chromatography. The anti-psoriatic efficacy was studied in the imiquimod (IMQ)-induced mouse model on the basis of morphological evaluation, psoriasis area and severity index calculation (PASI), and inflammatory cytokine expression. RESULTS: The average particle size of the blank β-CDs/CeO(2) NPs was 60.89±0.32 nm with a polydispersity index (PDI) of 0.12, whereas that of the DIT-loaded NPs was 79.38±1.06 nm with a PDI of 0.27. TEM results showed the as-prepared NPs formed a uniform quasi-spherical shape with low polydispersity. XPS indicates synthesized NPs have a mixed Ce(3+)/Ce(4+) valence state. FTIR spectroscopy confirmed the presence of β-CDs and DIT in the NPs. Inhibition of superoxide anion rate by NPs could be reached to 79.4% in the presence of 200 µg/mL, and elimination of H(2)O(2) efficiency reached about 50% in the presence of 40 µg/mL, demonstrating excellent superoxide dismutase- and catalase-mimicking activities, thereby providing remarkable cryoprotection against ROS-mediated damage. Furthermore, β-CDs on the surface endowed the NPs with drug-loading function via host–guest interactions. The entrapment efficiency and drug loading of DIT are 94.7% and 3.48%, respectively. The in vitro drug release curves revealed a suitable release capability of DIT@β-CDs/CeO(2) NPs under physiological conditions. In IMQ-induced psoriatic model, the DIT@β-CDs/CeO(2) NPs exhibited excellent therapeutic effect. CONCLUSION: This study may pave the way for the application of nanozyme β-CDs/CeO(2) NPs as a powerful tool for psoriasis therapy.